Unjust enrichment: value, rights, and trusts - Swadling, W (Sweet and Maxwell, 2021)
Assesses the validity of academic claims that unjust enrichment includes enrichment both as value and rights, and therefore provides a basis for proprietary rights to restitution, generally as a trust. Suggests why such claims for imposing trusts appear misconceived, and why courts should instead permit orders for specific restitution of rights obtained as unjust enrichment.